Tantangan dan Strategi Praktis Pemertahanan Bahasa Lampung - Inawati, Iin (JURNAL PESONA, 2017)
AbstractÂ This article discusses Lampung language in the case of the challenge and the solution of its effort. There are at least five major problems in the existence of the Lampung language, namely: 1) a smaller population compared to migrants; 2) lack of pride of Lampung tribe people using Lampung language; 3) the use of Lampung language is limited to certain contexts, 4) the shift in the use of mother tongue in the family, 5) the trap of teaching the Lampung language on the teaching of script and not communication in the language of Lampung. The government has employed some ways to solve the problems. However, practical solutions can also be done by various parties, such as the family, school, and community.Keyword: Lampung language, Lampung tribe people, problems, challenge, solution.